KEPUTUSAN KONSUMEN DALAM MEMILIH PERUSAHAAN SEBAGAI DAMPAK DARI KELOMPOK REFERENSI DAN NILAI TERHADAP CITRA PERUSAHAAN ASURANSI UMUM DI PROVINSI DKI JAKARTA - Ismayudin Yuliyzar (JMB : Jurnal Manajemen dan Bisnis, 2018)
The objectives of this study are: (1) to analyze the effect of perceivedvalue on the company image and its implication to the decision in usinggeneral insurance product (2) to analyze the influence of refractiongroup to the company image and its implication to the decision in usinggeneral insurance product perceived and refresni groups to the companyimage and its implications for the decision in using general insuranceproducts. this research is descriptive and verifikatif. Respondents were235 customers. The results of this study are: (1) Partial reference grouphas a positive effect is not significant to Purchase Decision (2) The valueperceived by customers partially have a positive and significant impacton Corporate Image (3) Reference Group and Value Perceived Customertogether positive and significant to the image of General InsuranceCompany in Jakarta with the value of determination coefficient (R2) of48%. (4) Reference group by partial have positive and significant effectto Purchasing Decision, (5) The value of customer perceived by partiallyhave a positive and significant effect to Purchasing Decision (6)Corporate Image partially have positive and significant influence toPurchase Decision (7) Reference Group , Perceived Value of Customers,and Corporate Image together have a positive and significant effect onPurchasing Decision on General Insurance in DKI Jakarta with value ofcoefficient of determination (R2) equal to 83%.